THE DERIVATIVE OF FUNCTIONS AND THE CEILING DETERMINANT OF A SQUARE MATRIX - Tilahun Muche; Willie Reynolds (IJRDO -JOURNAL OF MATHEMATICS, 2021)
Derivatives in calculus and Determinants of square matrices of any size in linear algebra areextensively used in STEM, Financial and Business elds to mention some. In this researchpaper, we develop mathematical formula to drill determinants for evaluating the derivativesof a function of higher order n. First, we introduce the Ceiling Determinant of a two bytwo matrix and extended this denition to nd the derivative of a function of n order. Thisnew approach will help students to easily memorize the formula and apply to their majoracademic discipline. We have application examples on complex variable and geometry.